2007
DOI: 10.1152/ajplung.00126.2007
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal hypoxia triggers alterations in K+channels of adult pulmonary artery smooth muscle cells

Abstract: August 24, 2007; doi:10.1152/ajplung.00126.2007.-Adverse events during the perinatal period, like hypoxia, have been associated with adult diseases. In pulmonary vessels, K ϩ channels play an important role in the regulation of vascular tone. In the fetus, Ca 2ϩ -activated K ϩ channels (K Ca) are predominant, whereas from birth voltage-gated K ϩ channels (K V) prevail in the adult. We postulated that perinatal hypoxia could alter this maturational shift and influence regulation of pulmonary vascular tone in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…In the present study, whole-cell recording demonstrated a significantly decrease in BK channel current density in MA myocytes from Hy offspring, similar to the previous report on the renal interlobar artery myocytes following prenatal hypoxia [49]. However, an early study demonstrated that prenatal hypoxia increased whole-cell BK channel current density and BK channel α-subunit expression in pulmonary artery smooth muscle cells from male mice offspring [50]. The nature of those discrepancies may be caused by differences in animal strain, various organ used, and hypoxia conditions.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, whole-cell recording demonstrated a significantly decrease in BK channel current density in MA myocytes from Hy offspring, similar to the previous report on the renal interlobar artery myocytes following prenatal hypoxia [49]. However, an early study demonstrated that prenatal hypoxia increased whole-cell BK channel current density and BK channel α-subunit expression in pulmonary artery smooth muscle cells from male mice offspring [50]. The nature of those discrepancies may be caused by differences in animal strain, various organ used, and hypoxia conditions.…”
Section: Discussionsupporting
confidence: 90%
“…24,25 Most studies on the effect of hypoxia on BK Ca were conducted in pulmonary arteries. 26,27 Because our previous studies suggested that H-R impairs EDHF-mediated relaxation in both coronary microarteries and cardiac veins, 18,19,28,29 in the present study we investigated the effect of ischemia on the EDHF-targeting channels in VSMC BK Ca , by using the patch-clamp technique and isometric force measurement.…”
Section: Discussionmentioning
confidence: 99%
“…However, to control that the inhibitory effect of BEL on endotheliumdependent relaxations is not due to a direct effect on smooth muscle, the effect of iPLA 2 inhibition with BEL was investigated on the endothelium-independent relaxation triggered by the NO donor DEA/NO (26). As shown in Fig.…”
Section: Ipla 2 Inhibition Does Not Impair the Endothelium-independenmentioning
confidence: 99%